THE RELATIONSHIP BETWEEN STROKE SEVERITY LEVEL AND THE NEEDS OF ACTIVITY OF DAILY LIVING (ADL) FULFILLMENT AT THE NERVE POLYCLINIC, SLEMAN HOSPITAL, YOGYAKARTA - Dewi Khiftiani; Ruhyana; Sigit Harun (Journal of Indonesian Anesthesiology Nursing, 2024)
ABSTRACT Background: Stroke is a nervous disorder characterized by the obstruction of blood vessels. The Clots that formed in the brain and disrupted blood flow block arteries and cause blood vessels to burst that lead to bleeding. Methods: : This research was a quantitative correlation descriptive research with a cross sectional approach. The sample for this research was 90 stroke patients at Sleman Hospital, Yogyakarta. The sampling technique in this research was random sampling. The data analysis performed was Spearman rank test data analysis technique. Results: The highest number of patients with mild neurological deficits was 32 people (35.6%) from all of stroke patients. Meanwhile, to fulfill ADL needs, the condition of most patients was in the mild dependency category; and the number was 43 patients (47.8%). The p-value was 0.685 (p>0.05). Thus, it could be concluded that Ha was accepted, which meant that there was a relationship between the severity level of stroke and the fulfillment of activity of daily living (ADL) needs at the Yogyakarta Neurology Polyclinic. Conclusion: There is a strong relationship between stroke severity level and the fulfillment of activity of daily living (ADL) needs at the Neurology Polyclinic, Sleman Hospital, Yogyakarta with a p value <0.05.